A new numerical method for evaluating the variation of casing inner diameter after strike‐slip fault sliding during multistage fracturing in shale gas wells. Issue 5 (23rd July 2019) - Xi, Yan; Li, Jun; Liu, Gonghui; Zha, Chunqing; Zeng, Xiamao; Zhong, Wenli
Abstract: Casing shear deformation has become a prominent problem in the process of completion in shale gas wells. It was believed that the slide of strike‐slip fault induced by multistage fracturing was the main reason. This paper presented a new numerical investigation for evaluating the casing inner diameter after strike‐slip fault sliding based on the microseismic data. A 3D finite element model, considering the mechanical anisotropy of shale and heat‐fluid‐solid coupling effect during multistage fracturing, was developed to calculate the variation of casing inner diameter after fault sliding under different engineering and geological conditions. The calculation result was verified by comparison with the measurement result of the multi‐finger caliper survey. Sensitivity analysis was carried out and the results showed that decreasing the sliding distance, maintaining high pressure, increasing the casing thickness, and increasing the elasticity modulus and decreasing the Poisson ratio of cement sheath were beneficial to protect the casing integrity. Finally, the engineering verification demonstrated that the numerical method has an accuracy up to 85.9%. Numerical model in this study was expected to provide a better understanding of casing shear deformation and an evaluation method of casing inner diameter after fault sliding during multistage fracturing in shale gas wells. Abstract : In this study, the relationship between microseismic moment magnitude and sliding distance was established. A 3D numerical model, considering the mechanical anisotropy of shale and heat‐fluid‐solid coupling effect during multistage fracturing, was developed to quantify variation of casing inner diameter after fault sliding. The calculated result was verified by comparison with the measurement result of the MFC survey.